Anatomicosurgical arterial segmentation of the cat lungs (Felis catus domesticus, L., 1758) - OLIVEIRA, Fabrício Singaretti (2001)
The aim of this research was to establish the anatomicosurgical segments through lobation and arterial intralobar branching in cats lungs. After dissection of twenty lungs, it was noted that the right pulmonary artery, usually, emits a branch to the cranial lobe and a branch to the middle lobe, arising together from a trunk. A large branch irrigates the caudal lobe in most of the cases. Two branches arising in common origin from the caudal lobe branch irrigate the accessory lobe. The left pulmonary artery originates a trunk that, in most of the cases, emits a branch to the cranial and a branch to the caudal part of the left cranial lobe. It can be concluded that the right lung is formed by four and the left by two lobes, and variations occur in the pulmonary arterial branching.